A theoretical model for calculation of biphase composite failure energy - Popov, A.Yu.; Kazo, I.F.; Makara, V.A. (Functional Materials, 2005)
А conjunction of two approaches to the estimation of composite material strength characteristics is reported. The first approach is based on taking into account the influence of crack front bending between two stoppers (delay sites). In this case, the strength is increased because of the additional energy expenditure for the crack front elongation. The second approach is based on the evaluation of the influence of physical and mechanical characteristics of both phases as well as upon the character of the stopper overcoming. The presented model has been used to calculate the failure energy of S₃N₄-SiC composite with different grain size ratios. В работе представлено объединение двух подходов к оценке прочностных характеристик композиционных материалов. Первый подход основан на учёте выгибания фронта трещины между двумя местами задержки (стопорами). При этом прочность повышается в результате добавочных энергетических затрат на удлинение фронта. Сущность второго подхода заключается в учёте влияния механических характеристик обеих фаз на характер преодоления трещиной стопоров. Представленная модель использована для оценки энергии разрушения композита S₃N₄-SiC с разными соотношениями размеров зерен обеих фаз. У роботi представлено об'єднання двох пiдходiв до оцiнки мiцнiсних характеристик композицiйних матерiалiв. Перший пiдхiд засновано на урахуваннi вигинання фронту трiщини мiж двома мiсцями затримки (стопорами). При цьому мiцнiсть пiдвищується у результатi додаткових енергетичних витрат на видовження фронту. Сутнiсть другого пiдходу полягає у врахуваннi впливу механiчних характеристик обох фаз на характер подолання трiщиною стопорiв. Представлена модель використана для оцiнки енергii руйнування композита S₃N₄-SiC iз рiзними спiввiдношеннями розмiрiв зерен обох фаз.